A gendered assessment of crop traits to improve breeding product design and uptake: the case of potato in Kenya - Mutiso, J.M.; Mayanja, S.; Nyaga, J.; Sinelle, S.; Renou, C.; Onyango, C.; Hareau, G.; Polar, Vivian; Ashby, Jacqueline A.; Okello, J.J. (Frontiers Media, 2024)
The study assesses the gender implications of a target product profile for table potato in Kenya. Breeding programs mostly emphasize farmers’ trait requirements and rarely pay attention to other value chain actors’ preferences. This partially contributes to the low uptake of improved varieties. Therefore, efforts are required to assess the gender implications of crop product profile proposals during development, testing, and dissemination. In this paper, we assess the gender implications of traits targeted by a potato breeding program in Kenya using the G+ tools. The study applies the G+ product profile tool to examine the instances the selected traits may exacerbate gender disparity along four domains: unpaid labor, access to employment opportunities, requiring extra inputs and control over benefits. We use mixed methods including a review by social scientists, key informant interviews and a multistakeholder workshop to gather insights from female and male farmers, breeders, and other stakeholders. Findings show that pest, disease resistance, and shelf-life traits benefit women and men in the target customer segments. On the other hand, earliness, dry matter, and yield could increase drudgery for women. The traits increase demand for women’s unpaid labor during harvesting, sorting and food preparation time while also displacing women from profitable nodes. We recommend that gender-responsive strategies accompany the release of the target variety to mitigate inequities and enhance adoption.